Pre-Plant Nitrogen Rate and Application Method and Side-Dress Nitrogen Rate Effects on Corn Grown No-Till on a Claypan Soil - D. W. Sweeney; D. Ruiz-Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
Corn yield in 2018 was increased by about 5 bu/a with knife application of pre-plant nitrogen (N) fertilizer compared with broadcast application. Fertilizing with increasing rates of N applied pre-plant, at side-dress, or both had little effect on yield or yield components of corn in 2018.
Keywords: nitrogen; pre-plant; side-dress; corn; no-till